Nova renascença - propr. da Associação Cultural Nova Renascença (Nova Renascença)
Existências: V. 1 nº 2 (Inv 1981) - V. 2 nº 5 (Outono 1981); V. 3 nº 9 (Outono 1982/Inverno 1983) - V. 3 nº 10 (Outono 1981); V. 5 nº 19 (Jul-Set. 1985) - V. 5 nº 20 (Out.-dez. 1985); V. 6 nº 22 (Abr.-jun 1986); V. 7 nº 25 (jan.-mar. 1987) - V. 17 nº 64-65 (Inverno/Verão 1997); V. 18 nº 69-71 (Primavera/Outono 1998).